Design of transmission system by electromagnetic transient simulation : a case study of Son La-Hoa Binh-Nho Quan 500 kV transmission lines and substations - Le Xuan Hoa; Nadarajah, Mithulananthan; Weerakorn Ongsakul; Wang, Yaw-Juen; Electricity of Vietnam (EVN); Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
The 500kV transmission system in Vietnam plays an important role in transferring bulk of energy from one region to the others depending on the seasons. As of now, there are only eleven 500kV substations and 3302km of 500kV transmission lines. There are more 500kV transmission substations and lines planned for the future as the total demand growing at a very high rate. This thesis tries to address some of the design for a new 500kV transmission system in the North part of Vietnam. This transmission system knows as Son La-Roa Binh-Nho Quan consists of three substation and two transmission lines. A number of electromagnetic transient simulations have been carried out to find the parameters related to neutral circuit of shunt reactor, transient recovery voltage and closing resistor of line circuit breaker and line surge arrester
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering in Energy
Thesis (M.Eng.) - Asian Institute of Technology, 2008
Keywords: Electromagnetic waves -- Transmission